2010
DOI: 10.1007/s00251-010-0489-1
|View full text |Cite
|
Sign up to set email alerts
|

The −159C/T polymorphism in the CD14 gene and the risk of asthma: a meta-analysis

Abstract: The -159C/T polymorphism in the CD14 gene has been implicated in susceptibility to asthma, but a large number of studies have reported inconclusive results. The aim of this study is to investigate the association between the -159C/T polymorphism in the CD14 gene and the risk of asthma by meta-analysis. We searched Pubmed, Embase, CNKI database, Wanfang database, Weipu database, and Chinese Biomedical database, covering all publications (last search been performed on April 20, 2010). Statistical analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
1
16
1
Order By: Relevance
“…The mixed asthma was an overly broad collection of different phenotypes, which may have unknown underlying confounding factors to not reveal a credible relationship. Interestingly, the pooled results of this study were inconsistent with the results of previous meta-analysis, [24,25] which showed that the TT and TC genotypes were associated with decreased risk of atopic asthma compared with CC in Asian and children. The following reasons may be plausible explanation of the contradictory results: the small sample was included in the 2 meta-analyses, so the results may reveal an unreliable association, also there are 18 case–control studies including 7029 subjects eligible for this meta-analysis among atopic asthma, therefore the result of this meta-analysis may be closer to the real value; there is a lack of golden standard for asthma phenotype definitions, resulting in the misclassification of cases and reduction of statistical power, besides, as we know, several other risk factors, including different environmental exposure, clinical information, and further subtypes, may have an effect on the results and contribute to moderate heterogeneity; and different genotyping methods and various experimental protocols, and different life backgrounds may make these results incredible.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The mixed asthma was an overly broad collection of different phenotypes, which may have unknown underlying confounding factors to not reveal a credible relationship. Interestingly, the pooled results of this study were inconsistent with the results of previous meta-analysis, [24,25] which showed that the TT and TC genotypes were associated with decreased risk of atopic asthma compared with CC in Asian and children. The following reasons may be plausible explanation of the contradictory results: the small sample was included in the 2 meta-analyses, so the results may reveal an unreliable association, also there are 18 case–control studies including 7029 subjects eligible for this meta-analysis among atopic asthma, therefore the result of this meta-analysis may be closer to the real value; there is a lack of golden standard for asthma phenotype definitions, resulting in the misclassification of cases and reduction of statistical power, besides, as we know, several other risk factors, including different environmental exposure, clinical information, and further subtypes, may have an effect on the results and contribute to moderate heterogeneity; and different genotyping methods and various experimental protocols, and different life backgrounds may make these results incredible.…”
Section: Discussioncontrasting
confidence: 99%
“…[2123] So far, 2 earlier meta-analyses based on different strategies have tried to detect the possible association of CD14 −159C/T polymorphisms with asthma. [24,25] Unfortunately, the former had several noteworthy errors pertaining to study inclusion, data abstraction. [24] The latter had included 3 articles which deviated from Hardy–Weinberg equilibrium (HWE).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated that CD14 rs2569190 may be associated with asthma. This association has been analyzed in two metaanalyses (Zhang et al, 2011;Zhao and Bracken, 2011). No significant overall association was found between rs2569190 and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that polymorphisms in the CD14 gene are associated with atopic asthma [11], but more importantly, there is emerging evidence that these polymorphisms modify the effect of endotoxin on atopy and atopic disease. This may, to some extent, explain some of the reported inconsistencies in the association of endotoxin with disease.…”
mentioning
confidence: 99%